PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI MOTIVASI DAN KOMITMEN DENGAN DIMODERASI OLEH BUDAYA ORGANISASI Ken Sudarti - Ken Sudarti; Desy Arijani (LPPM STIE DHARMAPUTRA SEMARANG, 2012)
ABSTRACTThis study aims to analyzethe influence of motivation, employee commitmentand organizational culture on the performance of human resources. thecooperative micro small and medium office of Central Java province hasimportant duty and function to formation or mentoring cooperative microsmall and medium, it is necessasry to review the extent of these factorscanimprove the performance of human resoyrces in optoimizing their duty.Population of this study is all officer of the cooperative micro small andmedium office of Central Java province amounted to 162, an this study took asample of 110 respondents. Analysis results by using multiple linearregression showed that motivation has a positive effect on organizationalcommitment and human resources performance enhancements, andcommitment has a positive effect in improving the human resourcesperformance and application of of organizational culture influence inmoderating the existing structure for enhanced human resourcesperformance.Keywords: human resources performance, motivation, employee commitmentand organizational culture.